Self Inserted Foreign Rectal Body – Systematic Review - Bernardus Parish Budiono; Abdul Kholid; Sigit Adi Prasetyo (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Self-inserted foreign rectal bodies (SIFRBs) represent an uncommon but increasingly reported clinical entity presenting to emergency departments. These cases pose diagnostic and therapeutic challenges due to patient embarrassment, delayed presentation, wide variability of inserted objects, and the potential for severe colorectal complications. A comprehensive synthesis of current evidence is needed to guide safe and effective management. Methods: A systematic literature review was conducted following PRISMA guidelines. Searches of PubMed, Medline, Scopus, Web of Science, and Google Scholar were performed on March 1, 2025, using combinations of the terms “rectal,” “colorectal,” “colon,” and “foreign body.” Articles published in English, German, Italian, and French reporting demographic data, diagnostic approaches, and therapeutic management of SIFRBs were included. Duplicate records, non-human studies, editorials, and studies lacking sufficient clinical data were excluded. Of 1,180 identified records, 10 studies met inclusion criteria, comprising systematic reviews, retrospective studies, and case reports. Results: SIFRBs predominantly affected male patients (85%), with a mean age of 42 years. Sexual stimulation was the most common motivation (72%), followed by psychiatric conditions and accidental insertion. Frequently reported objects included sexual devices, glass items, plastic containers, and food products. Diagnosis relied on careful history-taking, digital rectal examination, and imaging, primarily abdominal radiography and computed tomography. Non-surgical extraction was successful in approximately 65% of cases, while 35% required surgical intervention. Complications included rectal perforation, anal sphincter injury, infection, and bleeding. Conclusion: Management of self-inserted foreign rectal bodies requires a patient-centered, flexible, and multidisciplinary approach. While non-operative extraction is often successful, prompt recognition of complications and individualized treatment strategies are essential to minimize morbidity and optimize outcomes. Keywords : Rectal foreign body, self-inserted foreign body, emergency colorectal surgery, transanal extraction, rectal injury